Explaining MPs' constituency service in multilevel systems: the case of Belgium. Issue 4 (December 2016) - Brack, Nathalie; Pilet, Jean-Benoit
Abstract Political representation – the core of modern democracies – essentially refers to a relationship between a representative and those represented by him or her. Therefore, the linkage between citizens and political decision makers is one of the most important topics in the study of democratic political systems. However, the literature on parliamentary systems has concentrated on what MPs do inside parliament on the one hand and on the impact of the electoral system on MPs' behavior on the other hand. This aim of this article is twofold. First, it provides a more comprehensive description of the activities of Belgian MPs on the basis of a mixed-method approach, using data from a survey, interviews as well as field observations. Second, it addresses four other factors that could have an influence on MPs relations to the district, besides the electoral system: the level at which they are elected (regional vs. federal), the accumulation of mandates, the distinction between older and newer parties, and MPs seniority.